Pengaruh Social Media Marketing Instagram dan Brand Image terhadap Keputusan Pembelian - Gisyel Gabriena Putri; Dede R. Oktini (Bandung Conference Series: Business and Management, 2024)
Abstract. This research focuses on the variables of Instagram social media marketing, brand image, and purchasing decisions. The aim of this study is to determine the relationship between Instagram social media marketing, brand image, and purchasing decisions in the context of PT Pos Indonesia's courier services in Cianjur City. The method used in this research is a survey method with a questionnaire as the data collection instrument. The subjects of this research are users of PT Pos Indonesia's courier services in Cianjur City, totaling 96,04 people, which were then narrowed down based on sampling criteria to 100 people. The sampling technique used in this study is purposive sampling. There are two hypotheses in this research. The data analysis used includes descriptive and verificative analysis, employing classical assumption tests, correlation tests, multiple linear regression analysis, coefficient of determination, F-statistic tests, t-statistic tests, and the coefficient of determination. The results of this study indicate that Instagram social media marketing has a significant partial effect on purchasing decisions. Brand image also has a significant partial effect on purchasing decisions. Additionally, Instagram social media marketing and brand image, simultaneously, have a significant effect on purchasing decisions for PT Pos Indonesia's courier services in Cianjur City.Keywords: Social Media Marketing Instagram, Brand Image, and Purchasing Decisions Abstrak. Penelitian ini berfokus kepada variabel social media marketing instagram, brand image, dan keputusan pembelian. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara social media marketing instagram, brand image, dan keputusan pembelian pada jasa ekspedisi PT Pos Indonesia di Kota Cianjur. Metode yang digunakan pada penelitian ini ialah metode survei dengan instrumen kuesioner sebagai teknik pengumpulan datanya. Objek penelitian ini ialah pengguna jasa ekspedisi PT Pos Indonesia di Kota Cianjur berjumlah 96,04 orang yang dikerucutkan kembali berdasarkan kriteria sampling menjadi 100 orang. Teknik sampling dalam penelitian ini menggunakan purposive sampling. Terdapat dua hipotesis yang ada pada penelitian ini. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif menggunakan uji asumsi klasik, uji korelasi analisis regresi linier berganda, koefisien determinasi, dan uji statistic F, uji statistic t, dan koefisien determinasi. Hasil dari penelitian ini menunjukkan social media marketing instagram secara parsial berpengaruh signifikan terhadap keputusan pembelian. brand image secara parsial berpengaruh signifikan terhadap keputusan pembelian, serta social media marketing instagram dan brand image, secara simultan berpengaruh signifikan terhadap keputusan pembelian jasa ekspedisi PT Pos Indonesia di Kota Cianjur.